1998
DOI: 10.1103/physreve.58.6399
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative model of bacterial sensing

Abstract: Bacterial chemotaxis is controlled by the signaling of a cluster of receptors. A cooperative model is presented, in which coupling between neighboring receptor dimers enhances the sensitivity with which stimuli can be detected, without diminishing the range of chemoeffector concentration over which chemotaxis can operate. Individual receptor dimers have two stable conformational states: one active, one inactive. Noise gives rise to a distribution between these states, with the probability influenced by ligand … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 33 publications
2
62
1
Order By: Relevance
“…Cooperativity between receptors as a mechanism for the system's large gain was first suggested by Bray, Levin, and MortonFirth (8). Later, Shi and Duke (9) proposed an Ising-type model, where identical receptors on a regular extended lattice interact with their nearest neighbors, as a materialization of the idea. Duke and Bray (10) eventually implemented a Monte Carlo version of the simple Ising-type model and demonstrated that it is capable of enhancing the gain of the system.…”
Section: Motivation Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperativity between receptors as a mechanism for the system's large gain was first suggested by Bray, Levin, and MortonFirth (8). Later, Shi and Duke (9) proposed an Ising-type model, where identical receptors on a regular extended lattice interact with their nearest neighbors, as a materialization of the idea. Duke and Bray (10) eventually implemented a Monte Carlo version of the simple Ising-type model and demonstrated that it is capable of enhancing the gain of the system.…”
Section: Motivation Models and Methodsmentioning
confidence: 99%
“…Each receptor, T qm , is characterized by three parameters: q is the type of receptor, only the two high-abundance types of receptors with q ϭ 1 for Tar and q ϭ 2 for Tsr being considered in this paper, and the total number of Tsr being twice that of Tar; m ʦ [0, 4] is the number of methyl groups; and ϭ 0, 1 represents vacant and ligand-occupied receptors, respectively. We assume the probability of finding the receptor in the active or inactive state is controlled by their energy difference and obeys the Boltzmann distribution (9). The average activity for receptor T qm is then given by:…”
Section: Motivation Models and Methodsmentioning
confidence: 99%
“…A sensing apparatus is devoted to detecting information about the environment, by measuring concentration of chemicals (generally called, in this context, chemoeffectors). The arrangement and functioning of the receptors present on E. coli cellular membrane has been extensively investigated also from the theoretical point of view (see, e.g., [4,5]). The information collected by the receptors is transduced to the flagellar motors through the "messenger molecule" CheY.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on this issue are widely reported for various receptors, for example, integins, which attach cells to the extracellular matrix, tyrosine kinase receptors, cytoskine receptors, growth factor receptors, tumor necrosis factor receptors, including death receptors, antigen receptors such as T-cell receptors, bone morphogenetic protein receptor, G-protein-coupled receptors, etc [11][12][13][14][15][16][17][18][19]. In our previous works [2][3][4], the position of each receptor is fixed, and there is an a priori cluster. In the present article, we shall consider statistical mechanics of floating receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, thousands of receptors cluster together at a pole of the cell. Recently, based on detailed analyses on the experimental findings, I proposed that cooperative receptor-receptor interaction enhances the signalling, and constructed a statistical mechanical theory for this process [2][3][4]. My idea has since received considerable attention 1 .…”
Section: Introductionmentioning
confidence: 99%